Os quatro núcleos/eixos de produção da poética de Caio Fernando Abreu - Da Silva Dias, Ellen Mariany [UNESP] (Universidade Estadual de Maringa, 2008)
This article presents a short study about the literary work of Brazilian writer Caio Fernando Abreu (1946-1996). In order to study his formal and thematic choices, we established criteria based on concepts like motif and plot (dramatic situation), as developed by Tomachevski (1976). A specific articulation between motives and dramatic situations establishes four nuclei of Abreu's literary production, which is characterized by a literary experimentation with these elements and it constructs an organic work that makes itself and/or is made in a dialogic way (Bakhtin, 1981). Firstly, the main characteristics of the four nuclei and the books that embody them will be presented. Then, we will describe how the motives and dramatic situations are re-elaborated from one nucleus to another. Not only does each nucleus features some new elements, but also contains remainders of previous ones. As such, each of Abreu's works can be considered as both the same and unique.
Four nuclei/axes of meaning production in Caio Fernando Abreu's literary work
Keywords: Caio Fernando Abreu; Dialogism; Experimentation; Identity